A Thematic Commentary on the Qur’an - Mahan Mirza (International Institute of Islamic Thought, 2003)
There has been an increasing interest in the Qur’an’s literary aspects within the field of Qur’anic studies over the last few years. In the past, western scholars have devoted a great deal of energy to tracing foreign influences in the Qur’an or reconstructing the chronology of its verses and surahs. However, the trend now is shifting toward textual studies, a development indicated by the proliferation of articles, anthologies, and books on the Qur’an as a composed literary ornament. This shift is both refreshing and welcome, particularly for those who are more interested in understanding the Qur’an in its present form, rather than learning about its textual history or compilation. Classical Islamic scholarship developed a body of exegetical material on the Qur’an’s miraculous nature (i‘jaz) from a literary perspective. This approach has taken a primarily microscopic linguistic viewpoint (balaghah [eloquence]) of studying the choice of words and how the verses are constructed. Although it has always been accepted that the Qur’an’s surahs are distinct literary pieces with their own style and content, comprehensive attempts to present entire surahs as thematically independent entities have been rare. With increasing pressure from western scholars that the Qur’an is incoherent and haphazardly arranged, a new genre of exegetical material is developing, both in Muslim and western circles. This new genre focuses upon explaining why the surah should be considered as a distinctly composed piece with its own dynamic of sound and meaning. Muhammad al-Ghazali’s work falls within this emerging category of Qur’anic exegesis. A Thematic Commentary on the Qur’an is a translation from al- Ghazali’s Al-Tafsir al-Mawdu‘i. The print is well typeset and easily legible, not cramped together, with a glossy green cover commanding an elegance ...